Unilateral Absence of Mental Foramen with Surgical Exploration in a Living Human Subject - Murat Ulu; Elif Tarim Ertas; Fatih Gunhan; Meral Yircali Atici; Huseyin Akcay (Hindawi Limited, 2016)
The mental foramen (MF) is an important anatomic landmark of the mandible, in which the somatic afferent sensory nerve of the mandibular nerve emerges as mental nerve and blood vessels. The identification and actual location of MF are important in order to avoid sensory dysfunction or paresthesia due to mental nerve injury. In the literature there are some rare reports on the anatomical variations of the MF such as its location or presence of accessory foramina. The present report describes the absence of mental foramina on the left side of the mandible, as detected by cone-beam computed tomography before impacted tooth removal and observed directly during surgery.